Balanced Scorecard: A Systematic Literature Review and Future Research Issues. Issue 2 (June 2022) - Kumar, Jitender; Prince, Neha; Baker, H. Kent
This study provides a systematic literature review on the balanced scorecard (BSC), highlights gaps in the literature and identifies areas for further research. We review a sample of 114 BSC articles published in 14 accounting and 56 management journals between 1992 and 2021. Each article must either be in the Australian Business Deans Council (ABDC), Scopus-indexed or Academic Journal Guide (AJG) list, or receive at least 100 citations, as reported by Google Scholar. We separate the BSC literature into 11 major themes, examine the research methods, statistical tools used and identify the country affiliated with the authors. Companies typically use the BSC as a performance measurement system instead of a management control system. The BSC is more compatible with private versus public sector organizations. Successful implementation of the BSC requires support from the top management and effective communication and coordination. Additionally, a cause-and-effect relationship should exist among its four perspectives—customers, internal business, innovation and learning, and financial. BSC's critics question its superiority over other performance measurement tools. But the number of supporters is much higher than the opponents. Articles mainly focus on developed, not developing, countries and tend to be conceptual papers rather than data-based empirical studies. The most commonly used statistical tool used is regression analysis. Our review of BSC articles provides insights about BSC strategy, implementation, execution and control that should be of interest to researchers and managers. However, this qualitative study uses judgment to identify BSC themes.